Kritik Nalar Al-Jabiri ; Bayani, Irfani dan Burhani dalam Membangun Islamic Studies Integrasi-Interkoneksi - Muhammadun Muhammadun (Program Pascasarjana, Universitas Islam Bunga Bangsa Cirebon, 2019)
ABSTRACT The formulation of reasoning in religion, as well as the reformulation of its rationalism, must be based on doctrinal principles, clearly have a specific purpose and purpose, namely aimed at shari'ah makers (Allah and His Messenger) to humans which ultimately lead to human values. wisdom (al-fadilah). The point is that according to al-Jabri, the idea of